Rethinking the contractual context for Building Information Modelling (BIM) in the Australian built environment industry - Ilsa Kuiper; Dominik Holzer (Australasian Journal of Construction Economics and Building, 2013)
Building Information Modelling (BIM) can be defined as a process of generating and managing information of a building or infrastructure during its life cycle. Whilst the 3D visualisation or dimensional functions of BIM are not necessarily new, it is the usage and integration of this information related to project delivery, management and performance analysis that are challenging current construction industry practices.  Industry has called for the development of more collaborative and integrated contractual arrangements to facilitate the use of BIM. Such recommendations appeal to the ideal use of BIM, but also provide a potential opportunity to seek improvement within the construction industry. This paper proposes a procurement approach to BIM to establish the applicable contractual context to address the potential legal risks and commercial considerations, relative to current practices in Australia. It als ooutlines why BIM, with other enabling technologies, will drive the evolution of contract delivery methodologies.